A systematic study of the South African genus Prionium (Thurniaceae) - Munyai,Rabelani (Department of Biological Sciences, 2015)
The South African monocotyledonous plant genus Prionium E. Mey (Thurniaceae; Cyperid clade) is an old, species-poor lineage which split from its sister genus Thurnia about 33 - 43 million years ago. It is a clonal shrubby macrophyte, widespread within the Fynbos biome in the Cape Floristic Region (CFR) with scattered populations into the Maputaland-Pondoland Region (MPR). This study of the systematics of the genus Prionium investigates whether this old lineage comprising of a single extant species P. serratum, is morphologically, genetically and ecologically impoverished, and identifies apomorphic floral developmental traits in relation to its phylogenetic position as sister to the Cyperid families, Juncaceae and Cyperaceae. Sampling for morphological, molecular and ecological studies was done to obtain representatives from its entire distribution range, falling within the phytogeographic regions of the CFR (North West, NW; South West, SW; Agulhas Plain, AP; Langeberg, LB) and extending into Eastern Cape (South East, SE) and KwaZulu Natal (KZN). Samples for the floral ontogenetic study were collected to obtain representatives of the Cyperid clade families: Cyperaceae (Eriophorum, Scirpus), Juncaceae (Juncus, Luzula) and Thurniaceae (Prionium).